Post-Caldera Eruptions at Chalupas Caldera, Ecuador: Determining the Timing of Lava Dome Collapse, Hummock Emplacement and Dome Rejuvenation - Córdova, Marco D.; Mothes, Patricia Ann; Gaunt, H. Elizabeth; Salgado, Josué (Frontiers in Earth Science, 2020)
Determining the lithology, extent, origin, and age of hummocks can be challenging, especially if these are covered by successive deposits and lush vegetation. At Chalupas caldera, a late-Pleistocene silicic center that lies astride the Eastern Cordillera of northern Ecuador, we have tried to overcome these difficulties by combining geological observations and sampling, laboratory analysis (geochemistry, scanning electron microscope analysis and radiometric dating) and remote sensing techniques. Chalupas is the second largest caldera in the Northern Volcanic Zone of South America and its VEI 7 eruption, which occurred ∼0.21 Ma, has garnered the attention of the volcanological community. Our research highlights new observations of the post-caldera activity at Chalupas, beginning with the growth of Quilindaña stratovolcano (∼0.170 Ma), followed by the formation of Buenavista dome that is located 5 km eastward of Quilindaña’s summit. At the eastern foot of Buenavista dome we identify hummocky terrain covering an area of ∼20 km2. Collectively, the suite of techniques that we used helped to highlight geological features that shed light on the provenance of the hummocks and demonstrate that this topography may have originated from gravitational breccia flows from Buenavista lava dome. Numerical simulations were also performed to represent breccia flow transit and emplacement over the present caldera landscape and to view the potential hazard footprints of a future Buenavista dome collapse. For modeling we employed volumes of 20–120 Mm3 to visualize the consecutive traces of mass flow deposition and how the traces correspond to the hummocky landscape. Following the partial collapse of Buenavista lava dome, its rejuvenation is represented by tephra layers of several small eruptions that are dated at about 40 ky BP. These tephras represent some of the youngest eruptive activity recognized at Chalupas caldera. Our results contribute to the overall knowledge about Chalupas and demonstrate that eruptions at this important caldera are more recent than was previously reported.